Girls Gone Fundamentalist: Feminine Appeals of White Christian Nationalism - Mikkelsen, Sage; Kornfield, Sarah (Women's studies in communication, 2021)
GirlDefined Ministries is a flourishing multiplatform purity ministry developed by Texan sisters Kristen Clark and Bethany Beal. Clark and Beal's goal for GirlDefined Ministries is to develop a sisterhood that encourages women and girls to find their identity in what they imagine as God's design for femininity. Analyzing this discourse, we demonstrate how it mobilizes White supremacist strategies that have long nationalist histories within White Christian rhetoric in the United States. Moreover, we demonstrate how these strategies manifest in discourse through a particularly patriarchal version of femininity-thus, the sexism we identify in GirlDefined Ministries reinforces racial privilege for White people. Ultimately, we illustrate how this ministry utilizes rhetorical styles that first draw girls and women into an identity we describe as "pure White womanhood" and then deploy this identity on the front lines of the Christian culture wars.